A Values Framework for Measuring the Impact of Workplace Spirituality on Organizational Performance - Jurkiewicz, Carole L. (Journal of business ethics, 2004)
Growing interest in workplace spirituality has led to the development of a new paradigm in organizational science. Theoretical assumptions abound as to how workplace spirituality might enhance organizational performance, most postulating a significant positive impact. Here, that body of research has been reviewed and analyzed, and a resultant values framework for workplace spirituality is introduced, providing the groundwork for empirical testing. A discussion of the factors and assumptions involved for future research are outlined.